Perjuangan Pedagang Pasar: Mencari Ruang di Tengah Ketegangan dengan Polisi Pamong Praja. - Hasniar, Hasniar; Hasniah, Hasniah (JURNAL KABANTI: Kerabat Antropologi, 2025)
The conflict between market traders and the Civil Service Police has become a complex phenomenon in the management of public space in Anduonohu ??Market, Kendari City. This study aims to explore the dynamics and strategies used by traders in dealing with the enforcement by the Civil Service Police. The method used in this study is qualitative with in-depth interview techniques and direct observation of traders and law enforcement officers. The results of the study indicate that traders face serious challenges in maintaining their existence, with strategies such as securing merchandise and changing selling times as an effort to survive in the midst of the enforcement. In addition, this conflict reflects traders' dissatisfaction with inadequate legal awareness and infrastructure. This study implies the need for dialogue between related parties to achieve more constructive and sustainable solutions in market management.